The Students’ Attitude Towards English Classroom Environment of Madrasah Tsanawiyah Negeri Model Makassar 2018/2019 - Hanafi Pelu (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2019)
This research aims to find out the students’ attitude toward English classroom environment especially English teacher, English material and English classroom management. This research used descriptive method to find out the student’s attitude toward English teacher, English material and English classroom environment. The population of this research was the second-year students MTS Negeri Model Makassar. The sample technique of this study was random sampling which consists of 50 students.The instrument of this research was questionnaire by using mean score to find out the mean score of them xˉ=n1(x1+x2+50+xn). The result of data analysis of the questionnaire indicated that the students have positive attitude toward English teacher (59. 24 %), the students have positive attitude towards English material (53. 64 %) and the students have neutral attitude toward English classroom management (39%).